Digital Tools in Media Studies Analysis and Research. An Overview - Ross, Michael; Grauer, Manfred; Freisleben, Bernd (Medienumbrüche, 2009)
Digital tools are increasingly used in media studies, opening up new perspectives for research and analysis, while creating new problems at the same time. In this volume, international media scholars and computer scientists present their projects, varying from powerful film-historical databases to automatic video analysis software, discussing their application of digital tools and reporting on their results. This book is the first publication of its kind and a helpful guide to both media scholars and computer scientists who intend to use digital tools in their research, providing information on applications, standards, and problems.